Preeclampsia: The Need for a Biological Definition and Diagnosis - Vidaeff, Alex C.; Saade, George R.; Sibai, Baha M. (American Journal of Perinatology, 2020)
The centuries-old approach to the prevention of eclampsia and its associated maternal morbidity and mortality is based on the recognition of the presence of premonitory signs and symptoms such as hypertension and proteinuria. The spectrum of preceding signs and symptoms came to be known as preeclampsia, which is debatably considered to be an early stage on a clinical continuum possibly leading to eclampsia. The premonitory signs and symptoms were then construed as diagnostic criteria for the poorly understood syndrome of preeclampsia, and this led to a perpetual debate that remains subject to wide disagreement and periodic updates. In this commentary, we will draw attention to the fact that the criteria for preeclampsia should be viewed from the prism of a screening test rather than as diagnostic of a condition in itself. Focusing research on developing better diagnostic and screening methods for what is clinically important, namely maternal and perinatal morbidity and mortality from hypertensive disorders of pregnancy, a long overdue upgrade from what was possible centuries ago, will ultimately lead to better management approaches to what really matters.
Keywords: preeclampsia; definition; diagnosis; biomarkers